Horizontes do envelhecer: a geograficidade na obra Prantos, amores e outros desvarios, de Teolinda Gersão - SILVA, Rosângela Guedêlha da (2019)
This study aims to investigate the space through the geographic focus in the representation of old age in the literary work Prantos, amores e outros desvarios (2016), by the Portuguese author Teolinda Gersão. In order to do so, the tales ―As mimosas‖, ―Mal-entendidos‖, ―Vizinhas‖ and ―Água-marinha‖, will be analyzed since the textual tessitura of these narratives articulates the fictional subjectivity of the elderly characters with the objectivism of the real world, expressing human experiences with the space, which allow us to foresee attitudes of resistance in the context of the human condition of the elderly in the 21st century. This research, with a qualitative and bibliographical basis, seeks to bring closer, via the interdisciplinary bias, the Literature and the Humanist Cultural Geography, with a phenomenological nature, supported by the theoretical contribution of Yi-Fu Tuan, Eric Dardel, Gaston Bachelard and Edward Relph, with important contributions, mainly, of Simone de Beauvoir about old age and Zigmunt Bauman on human relations in the context of "liquid modernity". In this sense, the aesthetic resources used in textual tessitura will be focused as well as their articulation with the representation of the categories implied in the concepts of geography, such as: space, place lived world, home, topophilia, crowding, spaciousness, placeness, exile and landscape. It is expected, therefore, to demonstrate the interlacing between the tales‘ production of Teolinda Gersão and the place of the elderly people in contemporary world.